The effect of water-logging on citrus rootstocks - Ko, Weng Wah (MARDI, Cameron Highlands (Malaysia). Fruit Research Division) (Institut Penyelidikan dan Kemajuan Pertanian Malaysia (MARDI), 2013)
In low-lying areas, citrus are severely affected by the wet soil condition. The citrus varieties not only should be resistant to soil-borne diseases, but they should also be able to withstand the adverse effect of water-logging. Thus, 20 varieties of citrus rootstocks were evaluated for their growth performance in wet alluvial soil in Cameron Highlands to select those which are tolerant to water-logging. Citron (Citrus medica), Alenow (C. macrophylla) and Mexican lime (C. aurantifolia) did not survive in wet soils. Although Rangpur lime (C. limonia) was known to be tolerant to tristeza virus and Phytophthora collar rot disease, a few trees were affected by water-logging. Rough lemon (C. jambhiri) and Volkamer lemon (C. volkameriana) under water-logging condition showed chlorosis on the foliage and the trees eventually declined. The adverse condition predisposed the trees to Phytophthora infection causing necrosis and gummosis at the collar region of the trunk. Limau Langkat (C. suhuiensis) survived longer than Valencia sweet orange, but eventually it was also severely affected by Phytophthora collar and root rot disease. Rootstocks that were tolerant to water-logging were Cleopatra (C. reticulata var. reshni). Timkat (C. reticulata var. oleocarpa), Sunki (C. reticulata var. austera), Brazilian sour orange (C. aurantium), Poorman orange (C. grandis hybrid), Troyer citrange (Ponicrus trifoliata x C. sinensis). Swingle citrumelo (Poncirus trifoliata x C. paradisi) and the Poncirus trifoliata strains (Rubidoux, Pomeroy and Karatachi)